Identification of slow magnetic relaxation and magnetocoolant capabilities of heterobimetallic lanthanide-manganese metallacrown-like compounds. (1st July 2021) - Lutter, Jacob C.; Boron, Thaddeus T.; Chadwick, Katelyn E.; Davis, Andrew H.; Kleinhaus, Stephen; Kampf, Jeff W.; Zaleski, Curtis M.; Pecoraro, Vincent L.
Graphical abstract: The structures of two 3 d -4 f metallacrown-like compounds, a Dy4 Mn4 complex and two Ln6 Mn4 (Ln = Dy and Gd) complexes, are described and the magnetic properties are discussed. The dysprosium versions of each molecule display slow relaxation of the magnetization, while the gadolinium derivative is a potential magnetocoolent. Abstract: Two types of 3 d -4 f compounds are presented, [Dy III 4 Mn III 4 (OH)2 (O2 C2 H3 )3 (shi)4 (H2 shi)4 (Hsal)3 (DMF)4 ] . 3DMF (Dy-1 ) and [Ln III 6 Mn III 2 Mn IV 2 (shi)6 (Hshi)4 (H2 shi)2 (Hsal)4 (DMF)8 ] . 4H2 O (Ln-2 ) (Ln = Dy or Gd, H3 shi = salicylhydroxamic acid, H2 sal = salicylic acid). While neither Dy-1 and Dy-2 demonstrated a significant barrier to magnetization relaxation, out-of-phase ac magnetic susceptibility was observed in both cases. Gd-2 showed potential as a magnetocoolent with gravimetric entropy changes reaching a maximum of 18.89 J . kg −1. K −1 at 3 K and ΔH = 7 T. This value represents approximately 53% of the theoretical maximum.